IMPLEMENTASI WORKSHEET BERORIENTASI PEMBELAJARAN INKUIRI UNTUK MENGAJARKAN KETERAMPILAN PROSES SAINS MAHASISWA - Saidil Mursali; Titi Laily Hajiriah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
Learning science including biology is strived to lead to the formation of skills not only relies on conceptual mastery. So it is necessary to instill skills in students through teaching and learning activities, one of them is science process skills. FPMIPA IKIP Mataram students are currently future candidates for natural science educators who have the responsibility to train their students to achieve the expected learning outcomes. Science process skills are one of the life skills that a person must possess in facing competition in the 21st century. These skills can be trained through inquiry learning. This study aims to describe the students' science process skills after being taught using an inquiry-oriented worksheet. This type of research is a pre-experimental design with one shoot case study. Data collection techniques are observation and quantitative descriptive analysis. The results of this study indicate the science process skills of students who use an inkuri-based worksheet of 75.73 with good categories. Based on the results above, the conclusion of this research is the science process skills of students after the implementation of the inquiry-oriented worksheet on average reaches a good category.